KAJIAN KONSENTRASI AIR KELAPA MUDA DAN MACAM PUPUK KANDANG TERHADAP PERTUMBUHAN SETEK NILAM (Pogostemon cablin Benth.) - Sri Rejeki Agustinah (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2014)
The rseach is purpose to know the the Test Effect from the sourch of unripe coconut waters concentration and manure form and the interaction to the growth of nilam cutting. It is carried out on December 2012 â€“ April 2013 at Jatibaru,Cemani,Grogol Sukoharjo with the altitude is 09 m above the sea level. The experimental design used in researh was Randmized Completely Block Design in two factors and three repetitions.The first factor was unripe coconut waters concentration, consist of : 0%, 25%, 50% , and 75%, The second factor was manure form, consist of:cattle manure, chicken manure, goat manure. There were 12 combinations of treatments and each was repeated 3 times. Data of reseach analyzed with analyze of covarian using F test at 5% and continued with DMRT at 5% for significant different. The result shows that conentration of unripe coconut water is 25% was can increase the time of shoot emergence,shoot lenngth,leave of number,fresh weight of shoot.dry weight of shoot. TheÂ catlle manure,chicken manure,and goat manure are good to nilam cultivation. There is no interaction between of unripe coconut waters concentration and manure form to all variables observed.